Immobilization of protease in biopolymers (mixture of alginate-chitosan) - Rezakhani, Nakisa; Molaei rad, Ahmad; Parivar, Kazem; Khayati, Maryam; Etemadzade, Sareh (Archives of Advances in Biosciences, 2015)
The Protease enzyme breaks down protein into amino acids as its constructors. Protease immobilization onto appropriate support materials plays an essential role in various fields of technology including the food and detergent industries. Accordingly, improvement of protease immobilization has been highly regarded due to its applications in bio catalysis. Alginate and chitosan are natural polysaccharides that have been studied so extensively in enzyme immobilization.In this research, the physical immobilization of proteases in alginate-chitosan beads showed satisfactory activity and stability. These beads were prepared by adding protease-alginate dropping intoChitosan and Calcium chloride solution. Then proteases enzyme encapsulated in alginate-chitosan beads. In the end, the different conditions such as temperature, pH and stability of the enzyme were studied. The immobilized protease was optimized in temperature of 47°C and at pH 8.5. The results demonstrated that the protease enzyme immobilized in alginate-chitosan beads exhibits reasonable stability and good activity.